HUBUNGAN PENGETAHUAN MAHASISWA TENTANG MATA KULIAH MIKROBIOLOGI DENGAN SIKAP ILMIAH TERHADAP KESEHATAN - Niken (Unika Santu Paulus Ruteng, 2018)
Health is an investment to support economic development and has an important role in poverty reduction efforts. Education is an essential element in the development and improvement of the quality of human resources in addressing environmental problems. This research is conducted related to attitudes toward health such as knowledge about microbiology that discusses the life of microorganisms. This cognitive aspect has a close relationship with health, because the microorganisms that are the cause of disease in humans generally. The type of this study was observational analytic using survey method with correlational analysis, by collecting data on attitude toward health through attitude test or attitude scale. This research was conducted in December until the month of January 2016 and carried out on Stikes Syedza Saintika Padang campus. Population taken from a number of midwifery students who have followed the microbiology class of 2015 as many as 50 people. Samples taken as many as 25 people. The variable of this research consist of one independent variable (X) that is knowledge about microbiology, and one dependent variable (Y) attitude of student to health. Results obtained there is a significant relationship between the dimensions of cognition, affective and psychomotor of 0.7.